Priority Development Areas and "Industrialization 4.0": Do Not Overlap Trajectories - f. Galiullina, Gulia; Kuznetsov, Boris.; n. Fatkhutdinov, alex; B.Kuznetsova, svetlana (International Journal of Engineering and Technology, 2018)
The paper discusses the problems associated with the priority social and economic development areas (PSEDAs) in Russia. The special role of high technologies in production processes in the priority social and economic development areas is noted. Attention is drawn to the goal of "advanced" development and to the functions of technological innovation and technological infrastructures in various fields of activity required for it. The methodological and technological foundations of "advanced development" are considered. The priority development in the Russian Federation is viewed through the prism of â€œindustrialization 4.0â€, the industrial revolution developing in the USA and Germany. â€œIndustrialization 4.0â€ is a new model of development which marks the end of the industrial and socio-economic formations of the 20th century and the beginning of the 21st century. As a result of the study, barriers to the creation of priority social and economic development areas were identified: the lack of a systematic approach to the implementation of a new type of special areas and an advanced scientific and technical base as the foundation for development in the modern world; the existence of a serious conflict of interest between stakeholders of the priority development areas; dominant decision making on survival strategies. The authors proposed to establish goal-setting as an important component in the national innovation system of Russia and determine technological directions, levels, criteria, qualimetric indicators based on the parameters and trends of the industrial revolution 4.0. The priority social and economic development areas should be considered as an important tool for the adaptation of technological clusters of Russia to international trends, regulations, key parameters, seeking to change the catch-up paradigm with the paradigm of economic development.Â